2019
DOI: 10.1002/gj.3534
|View full text |Cite
|
Sign up to set email alerts
|

Magma chamber processes and geodynamic implications of the Pithora pluton, Bastar Craton, Central India

Abstract: The interaction between the coeval mafic and felsic magmas result in mixing, mingling, and chemical exchanges between both the end‐member magmas. We document the features relevant to the magma chamber processes and quantify the extent of mixing by means of detailed field, petrographic, mineral, and whole‐rock geochemistry from one of the less known granitic plutons from the Pithora region that forms part of the Kanker granite, Bastar Craton. The study area is composed of granite, granodiorite (mixed zone), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The granite variants mostly display sharp contacts (Figure 2F). Elangovan et al (2017Elangovan et al ( , 2020, have found that the mafic and felsic magmatism were coeval. These granites are variably deformed at places and form granitic gneisses.…”
Section: Field Relationships and Petrographymentioning
confidence: 99%
“…The granite variants mostly display sharp contacts (Figure 2F). Elangovan et al (2017Elangovan et al ( , 2020, have found that the mafic and felsic magmatism were coeval. These granites are variably deformed at places and form granitic gneisses.…”
Section: Field Relationships and Petrographymentioning
confidence: 99%